Health Literacy and Medication Adherence Among Patients Treated in a Free Health Clinic - Mark T. Sawkin; Sara J. Deppe; Joanie Thelen; Steven C. Stoner; Craig A. Dietz; Rafia S. Rasu (SAGE Publishing, 2015)
Background: A patient's health literacy is not routinely assessed during visits with a health care provider. Since low health literacy is a risk factor for poor health outcomes, assessing health literacy should be considered as part of the standard medical workup. Objectives: To evaluate the health literacy levels and medication adherence of patients treated by pharmacists in both the general medicine and the chronic care clinics at an urban free health clinic. Methods: Eligible patients from the free health clinic completed the Rapid Estimate of Adult Literacy in Medicine (REALM), a health literacy measurement tool, during their clinic visit in 2011. Medication adherence was self-reported by the patients. Results: A total of 100 patients participated (mean age = 48). The majority of participants were female (56%) and white (55%). Most (64%) of the patients scored at a high school reading level according to REALM. Only 21% of participants read at a seventh- to eighth-grade level. Overall medication adherence rate was 73%. Forgetting to take medication was the most popular reason given for nonadherence. Conclusion: Disease state and adherence were significantly related in patients with HIV/AIDS and hypertension. Patient's ethnicity was significantly associated with literacy levels ( P < .05). Although patients' literacy levels were not significantly associated with self-reported adherence in this population, availability of a patient's baseline health literacy level as a part of the medical record may help clinicians to individualize their interaction based on the patient's health literacy level in order to achieve better health outcomes, including improved medication adherence, especially for underserved populations.